PENGARUH PARTISIPASI PENYUSUNAN ANGGARAN PADA KINERJA MANAJERIAL YANG DIMODERASI SELF EFFICACY DAN MOTIVASI KERJA - Handrika, Dea; Wirakusuma, Made Gede (E-Jurnal Akuntansi, 2017)
The purpose of a company to compete in the business competition can be realized if the managerial performance had to be effective. The managerial performance already is running effectively is to use the level of activity of budget participation of managers to employees or employees. The aimed of this study was to determine the effect of budget participation on managerial performance with self-efficacy and motivation as a moderating variable. This research was conducted at the Rural Bank city of Denpasar. The samples were  42 people, using the technique of saturated samples. Data collected with questionnaire technique. The analysis technique used is regression analysis moderation or Moderated Regression Analysis (MRA) .The results show that the budgeting participation has no effect on managerial performance. Similarly, self-efficacy that can strengthen the effect of budget participation on managerial performance. Meanwhile, work motivation is able to weaken the influence of budget participation on managerial performance.
Keywords: budgeting participation, self efficacy, motivation and managerial performance